Intrarater Reliability of Accreditation Assessment for Early Childhood Education - Petrus Redy Partus Jaya; Theresia Alviani Sum; Felisitas Ndeot (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2023)
This study measured intrarater reliability between assessors of Early Childhood Education (PAUD) unit accreditation in the East Nusa Tenggara Province (NTT), Indonesia. In the 2022 PAUD unit accreditation assessment, 50 institutions across 15 districts in the NTT Province were sampled. The intrarater reliability testing technique used was the intraclass correlation coefficient (ICC). The results showed good agreement between Assessor A and Assessor B, with the ICC coefficient in the 2022 PAUD unit accreditation assessment in the NTT Province being relatively high with an estimated ICC of 0.644. However, the ICC coefficient between Assessor A and Validator, as well as between Assessor B and Validator, was in the moderate category with a moderate level of agreement. In addition, the study found a small effect size, indicating that subjective factors such as assessors' backgrounds and accreditation experience had a very small correlation with accreditation scores. Therefore, efforts should be made to improve agreement between Assessor A and Validator as well as between Assessor B and Validator to improve intrarater reliability in the PAUD unit accreditation assessment in the NTT Province.Penelitian ini mengukur reliabilitas intrarater antara asesor akreditasi satuan Pendidikan Anak Usia Dini (PAUD) di Provinsi Nusa Tenggara Timur (NTT). Dalam penilaian akreditasi satuan PAUD tahun 2022, 50 lembaga yang tersebar di 15 kabupaten di Provinsi NTT dijadikan sebagai sampel. Teknik pengujian reliabilitas intrarater yang digunakan adalah teknik intraclass correlation coefficient (ICC). Hasil penelitian menunjukkan tingkat kesepahaman yang baik antara Asesor A dan Asesor B, dengan koefisien ICC dalam penilaian akreditasi satuan PAUD tahun 2022 di Provinsi Nusa Tenggara Timur tergolong tinggi dengan besaran estimasi ICC 0,644. Namun, koefisien ICC antara Asesor A dengan Validator maupun antara Asesor B dengan Validator berada pada kategori sedang dengan tingkat kesepakatan yang moderat. Selain itu, dalam penelitian ini diperoleh nilai effect size yang kecil. Hal ini menunjukkan bahwa faktor subyektif asesor seperti lingkungan asal maupun pengalaman melakukan akreditasi berkorelasi sangat kecil terhadap skor akreditasi. Oleh karena itu, perlu dilakukan upaya-upaya untuk meningkatkan kesepakatan antara Asesor A dan Validator serta antara Asesor B dan Validator guna meningkatkan reliabilitas intrarater dalam penilaian akreditasi satuan PAUD di Provinsi Nusa Tenggara Timur.Kata Kunci:  Reliabilitas intrarater; Akreditasi; Pendidikan Anak Usia Dini